SAARC-ASEAN prospects and problems of inter-regional cooperation - Sen Gupta, Bhabani 1921- (South Asian Publishers, 1988)
On the South Asian Association for Regional Cooperation and Association of the South East Asian Nations; papers presented at a seminar held under the auspices of the Centre for Policy Research, New Delhi, Feb. 20-22, 1987.